PENERAPAN TEKNOLOGI KOMUNIKASI MULTIHOP UNTUK MONITORING KONDISI LAMPU PENERANGAN JALAN UMUM BERBASIS LORA: Teknik Telekomunikasi - Ade Rosta Paramitha, Nadila; Fadhli, Mohammad; Mujur Rose, Martinus (Teknik Elektro Polsri, 2023)
Street lighting is one of the public facilities that plays a vital role in providing safety and comfort for road users. Therefore, any problems that occur with street lighting must be handled quickly and precisely. To achieve this goal, this study proposes a system for monitoring the condition of street lighting using LoRa-based multihop communication technology. In this study, each street light unit is equipped with an ACS172 current sensor and a BH1750 light sensor to determine the damage that occurs to the street lights automatically. Data from these two sensors is sent using LoRa Ra-02 to the relay and then forwarded to the gateway. The gateway forwards the data to the Firebase server so that the results of monitoring public street lighting can be observed via the internet network. Based on the results of system testing, the street light units (sensor nodes) can communicate with relays up to a distance of 200 m and with gateways up to a distance of 400 m. The gateway can also properly send sensor data to the Firebase server, so monitoring results can be viewed online via a smartphone.